Laboratórios orientados à sustentabilidade nas cidades brasileiras - Carolina Mendo dos Santos (2024)
In view of the exponential growth of scientific studies and the creation of Living Labs (LL) in Brazil, there is also a demand for analysis of this reality in a country that is still developing. While studies on this theme in Europe and the United States are looking for ways to evaluate the positive social impact caused by a laboratory, in Brazil the importance of investigating the mechanisms of Brazilian LL for the possible consolidation of this methodology is still pointed out (SILVA; BALL; BIGNETTI, 2014; SILVA; BITENCOURT, 2018; SILVA; FRANZATO, 2018; AMORIM; MARK; FERNANDES, 2022; ANDRADE; ARAÚJO; SIQUEIRA, 2022). Considering that an LL is a driver of social innovation for a more sustainable development of cities, the following research question arises: What sustainability strategies have Living Labs adopted in Brazil? In order to answer this question, two articles were elaborated, where in the first an overview of Brazilian studies on LL and Urban Living Lab (ULL) was presented and in the second, there was a characterization of Brazilian LL in relation to their orientation to sustainability. Both works help to achieve the general objective of this study, which is to point out the approach to sustainability found in Brazilian Living Labs. As this is a descriptive and exploratory research, data collection was done in two stages, separated into secondary data and primary data, the latter through an online questionnaire answered by active Brazilian LL. The analysis of this content showed that Brazilian laboratories follow three major characteristics: real-life context; collaboration and innovation. And within each of the aspects presented, there are practices and social interactions that aim at a positive impact on society for a more sustainable development of cities. In addition, the important interaction between Brazilian LLs and HEIs, being one of the main reasons for creation, actor involved and target audience. However, it was analyzed that many laboratories still have gaps in their structuring, not allowing their true potential to be reached, and causing the intentions of sustainability not to be seen at first. This result directly affects the practice of this methodology, already consolidated in Europe, since Brazilian LLs use social innovation for the more sustainable development of cities without realizing this action. This work advances by bringing this perspective to light for a chain of new studies that may help in the consolidation and dissemination of Brazilian Living Labs.